KONSEP ISLAM BERKEMAJUAN DALAM PEMIKIRAN AHMAD DAHLAN DAN RELEVANSINYA TERHADAP PEMBAHARUAN PENDIDIKAN ISLAM MODERN - Jeny Rheka; Nurul Ilmi Adyana; St. Nurhayati Ali (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to analyze the concept of Progressive Islam in the thought of KH. Ahmad Dahlan and its relevance to the renewal of modern Islamic education. This study is motivated by the condition of traditional Islamic education, which tends to be conservative and still experiences a dichotomy between religious knowledge and general knowledge. Method: The study uses a qualitative method with a library research approach. Data is obtained through the analysis of various books, scientific journals, and previous research related to the thought of Ahmad Dahlan, Progressive Islam, and modern Islamic education. Results: The research results show that the concept of Progressive Islam emerged as an effort to renew the stagnant Islamic education system. Ahmad Dahlan viewed Islam as a religion that promotes progress, rationality, and the integration of knowledge. This idea was realized through the Muhammadiyah education system, which integrates religious knowledge and general knowledge and applies modern learning methods. Novelty: This study emphasizes that Ahmad Dahlan's concept of Progressive Islam has strong relevance in addressing the challenges of Islamic education in the era of globalization and digitalization. This concept can serve as a philosophical foundation for the development of Islamic education that is integrative, progressive, and adaptive to the times.